2013
DOI: 10.18268/bsgm2013v65n1a13
|View full text |Cite
|
Sign up to set email alerts
|

Active sinking at the bottom of the Rincón de Parangueo Maar (Guanajuato, México) and its probable relation with subsidence faults at Salamanca and Celaya

Abstract: Rincon de Parangueo is a Quaternary maar that had a perennial lake until the 1980s. The lake was gradually desiccated as a consequence of drawdown in the Salamanca-Valle de Santiago regional aquifer and now functions as a playa-lake. In contrast with the features observed in other crater-lakes in the region (La Alberca, Cíntora, and San Nicolás), which also dried up at the same time, the bottom of the Rincón crater displays clear evidence of active deformation associated with mass movement of lake sediments to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…1). These spectacular maars have attracted geoscientists for more than a century, who have studied them from the simplest morphological aspects (e.g., Ordóñez, 1900Ordóñez, , 1906 to their environmental attributes (Park, 2005;Armienta et al, 2008;Kienel et al, 2009;Aranda-Gómez et al, 2013) and their petrologic, geochronological, geochemical, and volcanological features (cf. Cano-Cruz and Carrasco-Núñez, 2009).…”
Section: Previous Work and Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…1). These spectacular maars have attracted geoscientists for more than a century, who have studied them from the simplest morphological aspects (e.g., Ordóñez, 1900Ordóñez, , 1906 to their environmental attributes (Park, 2005;Armienta et al, 2008;Kienel et al, 2009;Aranda-Gómez et al, 2013) and their petrologic, geochronological, geochemical, and volcanological features (cf. Cano-Cruz and Carrasco-Núñez, 2009).…”
Section: Previous Work and Geologic Settingmentioning
confidence: 99%
“…The quest to understand how this continental crust has influenced the composition and evolution of the Trans-Mexican volcanic belt magmas in the last 20 m.y. is also a major subject of debate, and many rather contrasting views have been advanced, including those that confer a fundamental importance Petrology and geochemistry of the Valle de Santiago lower-crust xenoliths: Young tectonothermal processes beneath the central Trans-Mexican volcanic belt www.gsapubs.org | Volume 6 | Number 5 | LITHOSPHERE to crustal contamination (e.g., Kudo et al, 1985;McBirney et al, 1987;Verma, 1999Verma, , 2000Verma, , 2001Verma and Hasenaka, 2004;Chesley et al, 2002;Cebriá et al, 2011), and others that minimize that role (e.g., Luhr and Carmichael, 1985;Wallace and Carmichael, 1999;Martínez-Serrano et al, 2004;Gómez-Tuena et al, 2006, 2013Straub et al, 2011). However, relevant data on the structure and composition of the crystalline basement (granitic and metamorphic rocks) beneath the Valle de Santiago volcanic field based on geological outcrops (e.g., Centeno-García, 2005), gravity and seismicity (Campillo et al, 1996;Molina-Garza and Urrutia-Fucugauchi, 1993;Urrutia-Fucugauchi and Flores-Ruiz, 1996), and rare deep-seated xenoliths or megacrysts (Righter and Carmichael, 1993;Aguirre-Díaz et al, 2002;Urrutia-Fucugauchi and Uribe-Cifuentes, 1999;Ortega-Gutiérrez et al, 2008a) are rather inconclusive, in contrast to the abundant and well-studied lower crust and mantle xenoliths that occur in many places of northern Mexico (Nimz et al, 1986;Ruiz et al, 1988;Hayob et al, 1989;Pier et al, 1989;Rudnick and Cameron, 1991;Schaaf et al, 1994;Aranda-Gómez and Luhr, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the occurrence of land subsidence and its effects [3][4][5][6][7][8][9][10]. Studies dealing with monitoring and detecting subsidence are numerous [11][12][13][14][15][16][17], as well as works addressed to land subsidence modeling for calculating the expected magnitudes and rates of subsidence for different scenarios [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Rincón de Parangueo was one of four maar craters nearby the locality of Valle de Santiago village that used to have a perennial lake and nowadays is partially occupied by a brine lake. During the 1980's progressive desiccation began as a consequence of water overdraft from the regional aquifer that used to feed the lake (Escolero-Fuentes and Alcocer-Duran, 2004; Aranda- Gómez et al, 2013). Detailed geologic mapping in the sediments of the lake bed shows clear evidence of rapid active subsidence contemporaneous to desiccation (ArandaGómez et al, 2010(ArandaGómez et al, , 2013Aranda-Gómez and CarrascoNuñez, 2014;Cerca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Water withdrawal in the aquifer system adjacent to the volcanic field has been pointed out as the cause for deformation and desiccation of the lake since the 1980's decade (Escolero-Fuentes and Alcocer-Duran, 2004;Aranda-Gómez et al, 2013;and references therein). Fragmentation of the country rock due to diatreme formation is likely to be contained within the maar-diatreme and less likely to propagate down to deeper levels into the feeder dike.…”
Section: Introductionmentioning
confidence: 99%